PERAN KELUARGA DALAM MEBENTUK KARAKTER ANAK - Samsul Arif (Universitas Muhammadiyah Jember, 2018)
Islam is considered as an early religious education because education for children is one of the main goals in the development of Islam. Family is the onset for children to grow and develop. The growth and development of children is characterized by maturity of organs from the age of the baby to adulthood. Meanwhile, family also constitutes an important part for children's education, especially in terms of character building and personality. Discussion about the development of children’s character and personality means we face a situation where culture and lifestyle of parents are highly influential in the process. The closest environment has the strongest influence in forming children's habits. The problems of this study were formulated as follows: 1. what is the role of the family in shaping children’s character? 2. What efforts does the family make in children’s character building? The purpose of this study is to describe the role and efforts of the family in shaping the character of children. The approach used was qualitative involving library research (literature). The results of the study showed that the role of the family in building children's character can be done through hearing, vision and the heart. While efforts that can be made by the family in shaping children’s character can be done through prompting aqeedah, teaching worship, raising social values, giving supervision and attention as well as maintaining physical and mental health.